VALIDATION OF THE RUSSIAN VERSION OF A QUESTIONNAIRE FOR THE ASSESSMENT OF UTILITARIAN INDICES IN PEDIATRIC PRACTICE. STAGE II - I. V. Vinyarskaya; V. V. Chernikov; R. N. Terletskaya; S. V. Shcherbakova; А. N. Fetisova ("Paediatrician" Publishers LLC, 2014)
Aim: To create the Russian-language version of the standardized international questionnaire Health Utilities Index (HUI) applicable for children's age, on the basis of the relevant international requirements to linguistic ratification and validation of tools. Patients and methods: 427 children of the first and 233 children of the second health group have taken part in the research. Average age of patients made10.8 ± 4.6 years. Criteria validity of the HUI questionnaire was assessed by comparison of patients' answers who had the different health status, a convergent validity - by comparison of the HUI attributes with scales of the PedsQL questionnaire, reliability - by calculation of Cronbach's alfa and the analysis of correlations between questions of the HUI classification. Results: Between the first and second health group there were significant distinctions on each attribute of the HUI questionnaire (p < 0.001). Average value of a number of the reduced attributes significantly differed depending on the state of health of patients: the worse the state of health is, the higher number of limited attributes is (p < 0.05). Significant correlations between the scales estimating similar concepts on questionnaires HUI and PedsQL are established. In assessment of the reliability Cronbach's according to the HUI3 and HUI2 system made 0.79 and 0.8, respectively. Significantcorrelations between the questions estimating identical attributes (sight, hearing, speech, cognitive abilities) are shown. The validity and reliability assessment executed for children with various state of health, allowed to assess all attributes of the HUI2 and HUI3 systems. The received results showed satisfactory psychometric properties of the new language version of a questionnaire. Conclusion: The offeredRussian version of the international questionnaire HUI is a validated tool for the development of utility coefficients for various chronic diseases in children, creation of the national catalogue of these coefficients, carrying out of clinical economic researches.